Fluoro-methyl sulfonated poly(arylene ether ketone-co-benzimidazole) amphoteric ion-exchange membranes for vanadium redox flow battery. (20th December 2017) - Liao, Junbin; Chu, Youqun; Zhang, Qi; Wu, Kai; Tang, Jun; Lu, Meizhen; Wang, Jianli
Abstract: In this work, amphoteric ion-exchange membranes (AIEMs) prepared from fluoro-methyl sulfonated poly(arylene ether ketone- co -benzimidazole)s have been systematically evaluated for their potential usage in all vanadium redox battery (VRB). Our investigation has demonstrated that the compacted structure originated from the self-assembly ionic cross-linking and the positive charged benzimidazole moiety in AIEM matrix could synergistically reduce the vanadium species cross-contamination. The self-discharge time of a single cell assembled with AIEM of optimized chemical structure is over 3 times longer than that with Nafion117, and a desirable conductivity/permeability trade-off can be achieved by tuning the content of benzimidazole moiety. Single cell assembled with the optimized AIEM exhibit higher battery efficiencies and lower capacity loss than that with Nafion117 at current densities of 30, 50 or 70 mA cm −2 . Furthermore, the AIEMs are able to tolerate the strong oxidizing VO2 + and remain intact for over 370 days, as revealed from ex -situ chemical stability tests. These findings strongly suggest that the as-prepared AIEM can be a good candidate for low-cost and high-performance separator in VRB application. Graphical abstract: The selectivity (a) and chemical stability (b) of 60 SPAEK-6F- co -x%BI (X = 0, 5, 10, 15, 20) and Nafion117 IEMs. Highlights: A series of amphoteric ion-exchange membranes (AIEMs) were prepared for VRBs. The resultant AIEM could achieve a desirable conductivity/permeability trade-off. VRB with optimized AIEM exhibits lower capacity loss than that with Nafion117. AIEM could remain intact in 1.5 M (VO2 )2 SO4 solution (aq.) for over 370 days.